Electrocrystallization of fibrous silver deposits from nitrate melts: Experiments and modeling - Murashova I.B.; Khramov A.P.; Zotin I.V.; Zaikov YU.P.; Zyrjanov V.G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Fibrous silver deposits have been obtained in molten nitrates on a moving cathode. Cylindrical silver cathode was lifted from the melt AgNO3-NaNO3-KNO3. It is found that the dimensions of the silver threads as well as their shape and thickness depend on the electrolysis parameters: the values of current and velocity of the cathode lifting. Systematic study of the silver dendrite structure has been performed on a scanning electron microscope. Geometric characteristics have been evaluated statistically and regression equations linking these constitutive properties of the deposits with the values of current and of lifting velocity have been obtained. A criterion for the description of dendrite shape under different conditions is proposed.